Hand-assisted laparoscopic nephrectomy as a minimally invasive option in the treatment of large renal specimens - M. Tobias-Machado; Alessandro Tavares; Pedro H. Forseto Jr; Joao P. Zambon; Roberto V. Juliano; Eric R. Wroclawski (International Brazilian Journal of Urology, 2005)
INTRODUCTION: We describe our experience with hand-assisted laparoscopy (HAL) as an option for the treatment of large renal specimens. MATERIALS AND METHODS: Between March 2000 and August 2004, 13 patients candidate to nephrectomies due to benign renal conditions with kidneys larger than 20 cm were included in a prospective protocol. Unilateral nephrectomy was performed in cases of hydronephrosis (6 patients) or giant pyonephrosis (4 patients). Bilateral nephrectomy was performed in 3 patients with adult polycystic kidney disease (APKD) with low back pain refractory to clinical treatment previous to kidney transplant. The technique included the introduction of 2 to 3 10 mm ports, manual incision to allow enough space for the surgeon's wrist without a commercial device to keep the pneumoperitoneum. The kidney was empty, preferably extracorporeally, enough to be removed through manual incision. We have assessed operative times, transfusions, complications, conversions, hospital stay and convalescence. RESULTS: The patients mean age (9 women and 4 men) was 58 years. Mean operating time was 120 ± 10 min (hydronephrosis), 160 ± 28 min (pyonephrosis) and 190 ± 13 min (bilateral surgery for APKD). There was a need for a conversion in 1 case and another patient needed a transfusion due to a lesion in the renal vein; 2 patients had minor complications. CONCLUSION: HAL surgery is a minimally invasive alternative in the treatment of large renal specimens, with or without significant inflammation.